KEABSAHAN PERKAWINAN SIRI DITINJAU DALAM PERSPEKTIF HUKUM INDONESIA DAN HUKUM ISLAM - Beni Agus Saputro; Arga Andhika Putra Wibawa; Suwardi Suwardi (Fakultas Hukum Universitas Narotama, 2023)
Often discussed about a marriage both according to the view of Islamic law and the view of Indonesian law. The meaning of marriage in question is that it is a form of implementation of the Sunnah of the Prophet based on the applicable Islamic law and one of the biological needs of humans that must be fulfilled by nature and has also been regulated in legal arrangements in Indonesia. Issues that arrangements in Indonesia. Issues that are increasingly rife, especially the existence of unregistered marriages or which can be described as marriages on the basis of liking each other without presenting several witnesses as the validity of the marriage. The problems that arise from this description are, first, what is the validity of betel marriage according to Islamic law and second, how is the validity of betel marriage according to Indonesian law. This study aims to reveal the validity value of an unregistered marriage from Islamic law and applicable law in Indonesia. This research uses a statutory approach, and a conceptual.approach